2019
DOI: 10.3168/jds.2018-14737
|View full text |Cite
|
Sign up to set email alerts
|

Volatile aroma composition of distillates produced from fermented sweet and acid whey

Abstract: Lactose within whey can be fermented and distilled to produce a potable distilled spirit. The aim of this study was to determine if acid and sweet whey types can be fermented and distilled using similar processes and to investigate differences in volatile aroma compounds for the 2 distillates. Fermentation and distillation of the 2 whey types progressed in a similar manner, using Kluyveromyces marxianus for the initial fermentation and a glass still fitted with a Vigreux column for the subsequent distillation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 40 publications
3
24
0
1
Order By: Relevance
“…On the other hand, although about 68% of dairy production was represented by milk (whole, partially skimmed and skimmed), its incidence in terms of virtual water consumption was extremely lower than that of cheese ( Figure 4 ). This result was in line with previous studies that evaluated the environmental impact of cheese production compared to other dairy products, finding that the cheese supply chain had the highest demands for raw materials, energy, and water [ 66 , 67 ]. Cheese production processing involves numerous steps that are both time-consuming and environmentally expensive [ 68 ], which make it the main product in the dairy industry due to its greater economic value.…”
Section: Resultssupporting
confidence: 91%
“…On the other hand, although about 68% of dairy production was represented by milk (whole, partially skimmed and skimmed), its incidence in terms of virtual water consumption was extremely lower than that of cheese ( Figure 4 ). This result was in line with previous studies that evaluated the environmental impact of cheese production compared to other dairy products, finding that the cheese supply chain had the highest demands for raw materials, energy, and water [ 66 , 67 ]. Cheese production processing involves numerous steps that are both time-consuming and environmentally expensive [ 68 ], which make it the main product in the dairy industry due to its greater economic value.…”
Section: Resultssupporting
confidence: 91%
“…This indicates that whey permeate may be a suitable medium for other recombinant E. coli strains or other recombinant microorganisms. In fact, multiple studies have demonstrated the ability of E. coli to metabolize the lactose within whey permeate [6,8,16,26,52]. It was reported in 2017 that an E. coli strain efficiently grew and fermented untreated whey permeate without nutritional supplementation in a pH-controlled bioreactor [51].…”
Section: Whey As a Feedstock For Microbial Pinene Productionmentioning
confidence: 99%
“…For example, α-pinene (75.6% of total terpenoids) is an important bicyclic terpenoid that is widely used in the fragrance industry and for the synthesis of a variety of chemicals, while it is mostly known for its pine odor [54]. D-limonene (1.8% of total terpenoids) is reported to be responsible for a citrus mint and could be derived not only from the resin but also from whey fermentation via the probiotic culture [55]. A similar aromatic effect can be provided via other monoterpenes also; for example, linalool (0.8% of total terpenoids) is known for its sweet floral orange odor, while 3-carene (0.7% of total terpenoids) is known for its sweet lemon odor [53,56].…”
Section: Effect Of Pistacia Terebinthus Resin On Volatile By-productsmentioning
confidence: 99%